2002
DOI: 10.1021/np020342d
|View full text |Cite
|
Sign up to set email alerts
|

New Bioactive Rosigenin Analogues and Aromatic Polyketide Metabolites from the Freshwater Aquatic Fungus Massarina tunicata

Abstract: Four new rosigenin analogues (massarigenins A-D; 1-4) and two new aromatic polyketide-derived secondary metabolites (massarinins A and B; 6, 7) and have been isolated from the freshwater aquatic fungus Massarina tunicata. The structures of these compounds were determined primarily by analysis of NMR data, and that of compound 1 was verified by X-ray crystallography. The known compound 4-(2-hydroxybutynoxy)benzoic acid (11) was also obtained, and its absolute stereochemistry was assigned. Several of these metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 24 publications
(81 reference statements)
1
66
0
Order By: Relevance
“…massarigenin A (5a), Scheme 1], later isolated from the same fungus. [6] The formation of the stable hemilactol 2a upon water addition to massarilactone A (2) was also observed. The absolute configurations of the new compounds 3-5 were assigned by comparison of the optical rotations with related natural products as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…massarigenin A (5a), Scheme 1], later isolated from the same fungus. [6] The formation of the stable hemilactol 2a upon water addition to massarilactone A (2) was also observed. The absolute configurations of the new compounds 3-5 were assigned by comparison of the optical rotations with related natural products as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 91%
“…The absolute configurations of the new compounds 3-5 were assigned by comparison of the optical rotations with related natural products as shown in Scheme 1. Coniothyrenol (6), named after the producing [ ‡] Biologically Active Metabolites from Fungi, 27. Part 26: Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of related compounds tabulated in "AntiBase" (Laatsch 2005) led to three compounds with the same molecular formula, massarigenin C, massarigenin D (Oh et al, 2003), and 6-epi-5′-hydroxy-mycosporulone (Fukami et al, 1999), each possessing stereochemical differences. An observed NOE correlation between H-6 with H-10 indicated a cis-1,3-diaxial-type orientation of these protons, while an NOE correlation between H-4 and H 3 -12 showed that 3 is the known compound, 6-epi-5′-hydroxy-mycosporulone.…”
Section: Chemistrymentioning
confidence: 99%
“…Six of the marine Massarina species were described from mangroves (Hyde et al, 1992), while two were described from the salt marsh plant Juncus roemerianus (Kohlmeyer et al, 1995a,b). The secondary metabolite chemistry of Massarina species is virtually unexplored; only one freshwater species, M. tunicata Shearer and Fallah, has been investigated and eleven new bioactive compounds have been recorded (Oh et al, 1999(Oh et al, , 2001(Oh et al, and 2003. Although limited data are available, these studies indicate that Massarina species are chemically productive.…”
Section: Introductionmentioning
confidence: 99%
“…Among fungi from the diverse environments, the freshwater aquatic fungi have received attention. For example, several recent studies identified that freshwaterderived fungi contain some unique biologically active metabolites such as decaspirones [4], gliocladines [5], resorcylides [6], pseudohalonectrins [7], massarinolins [8], ophiocerins [9], massarigenins [10] etc.…”
mentioning
confidence: 99%